Transformasi Pelayanan Madrasah Untuk Lansia: Studi Kasus Madrasah Ibnu Mas’ud Malaysia - Nurmubarok, Asep; Luthfiyana, Alfiyah (Journal of Education and Islamic Studies (JEIS), 2024)
This research aims to explore service management at the Ibnu Mas'ud Islamic Boarding School, Malaysia, an Islamic educational institution established specifically for the elderly. This Islamic boarding school is unique because it applies a housing concept where each student has their own house. Service management here includes administration, curriculum, and management of human resources and facilities, all of which focus on the quality of education and welfare of students. The research method used is a qualitative approach with a case study design. Data was collected through interviews, observation and documentation at Madrasah Ibnu Mas’ud. The research results show that Madrasah Ibnu Mas’ud offers an alternative religious education for the elderly with minimal services and simple rules. These institutions do not provide services such as paid meals or laundry, and do not enforce strict rules such as the use of certain languages or uniforms. It is hoped that the results of this study will provide insight and recommendations for improving service management in Islamic boarding schools, especially Ibnu Mas'ud Islamic Boarding School, as well as becoming a reference for other Islamic boarding school managers in developing effective and efficient management strategies. ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi manajemen pelayanan di Madrasah Ibnu Mas’ud, Malaysia, sebuah lembaga pendidikan Islam yang didirikan khusus untuk lansia. Madrasah ini unik karena menerapkan konsep perumahan di mana setiap santri memiliki satu rumah sendiri. Manajemen pelayanan di sini mencakup administrasi, kurikulum, dan pengelolaan sumber daya manusia serta fasilitas, yang semuanya berfokus pada kualitas pendidikan dan kesejahteraan santri. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi di Madrasah Ibnu Mas’ud. Hasil penelitian menunjukkan bahwa Madrasah Ibnu Mas’ud menawarkan alternatif pendidikan agama bagi lansia dengan layanan yang minim dan aturan yang sederhana. Institusi ini tidak menyediakan layanan seperti makanan atau laundry berbayar, dan tidak menerapkan aturan ketat seperti penggunaan bahasa tertentu atau seragam. Hasil studi ini diharapkan dapat memberikan wawasan dan rekomendasi bagi peningkatan manajemen pelayanan di Madrasah, khususnya Madrasah Ibnu Mas’ud, serta menjadi referensi bagi pengelola Madrasah lain dalam mengembangkan strategi manajemen yang efektif dan efisien.